UPAYA PREVENTIF TUBERCULOSIS DALAM PELAYANAN KEFARMASIAN DI FASILITAS KESEHATAN TINGKAT PRIMER: Studi Kualitatif - Hendy Ristiono; Dyah Aryani Perwitasari (Sekolah Tinggi Ilmu Kesehatan ISFI Banjarmasin, 2026)
Tuberculosis (TB) is an infectious disease that remains a global health problem, with a high mortality rate, exceeding that of HIV/AIDS. In Indonesia, the incidence of TB-HIV reaches 36,000 cases, while cases of drug-resistant TB (TB-RO) are estimated at 12,000. The role of pharmacists in pharmaceutical services at primary healthcare facilities is very important, especially in drug management and clinical pharmacy. However, their role in TB preventive efforts does not yet have clear implementation standards. This study aims to develop guidelines related to TB preventive efforts in pharmaceutical services at primary healthcare facilities. This study used a qualitative method through in-depth interviews with officials from the Directorate of Pharmaceutical Services of the Ministry of Health and the central board of the Indonesian Pharmacists Association. The interviews aimed to obtain preliminary data for the development of a questionnaire that was then used in a cross-sectional study of pharmacists in primary healthcare facilities. The results showed five main domains in TB preventive efforts by pharmacists, namely: roles in clinical pharmacy services, drug management, TB case finding, community empowerment, and TB management. This study is expected to serve as a basis for the development of standardized standards for the role of pharmacists in TB prevention in primary healthcare facilities to improve the effectiveness of TB services and control in Indonesia.